Implementasi Pembelajaran Akidah Akhlak dalam Pembentukan Profil Pelajar Rahmatan Lil ‘Alamin di MTsN 7 Malang - Isma Mufidah; Fita Mustafida; Eko Setiawan; Dian Mohammad Hakim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The cultivation of the Rahmatan lil-‘Alamīn Student Profile has become an essential agenda in strengthening character education within the Merdeka Curriculum, particularly in madrasahs that play a strategic role in fostering moderate, inclusive, and ethically grounded Islamic values. This study aims to analyze the Rahmatan lil-‘Alamīn values, values are integrated into the instructional, the assessment practices and student profiles embedded in the teaching of Akidah Akhlak at MTsN 7 Malang. Employing a qualitative case study design, data were collected through classroom observations, interviews with teachers and school leaders, and document analysis of curriculum materials and instructional plans. Data were analyzed using techniques of data reduction, data display, conclusion drawing, and triangulation to ensure credibility. The findings reveal that ten key Rahmatan lil-‘Alamīn values are integrated into both the planning and implementation of instruction through collaborative strategies, role modelling, case-based learning, and P5PPRA project activities. However, character assessment within intrakurikular learning remains limited and is largely conducted through cocurricular programs. This study contributes to the understanding of how character values are embedded in Islamic education and highlights the need to strengthen formative assessment practices in Akidah Akhlak instruction. It concludes that cultivating a Rahmatan lil-‘Alamīn student profile requires a comprehensive and continuous approach that aligns planning, practice, and assessment, and recommends future research across broader madrasah contexts and longitudinal designs to capture developmental character trajectories more fully.